Nothofagus forest dynamics and palaeoenvironmental variations during the mid and late Holocene, in southwest Patagonia - Echeverria, Marcos Emanuel (2014)
Southern Patagonia intersects the core of the Southern Westerlies, providing a unique opportunity for palaeo-reconstructions and the implication of past wind variations. There is a strong link between the strength of the westerlies and precipitation, which impacts vegetation communities. The palaeoenvironmental changes that occurred since the middle Holocene to present days are reconstructed from a peat record recovered in Peninsula Avellaneda (50°15′57″S; 72°50′33″W). Interpretations are based on pollen, charcoal and sediment analyses. Closed Nothofagus forest together with low fire activity characterized the region during the period c. 5500–3500 cal. yr BP, related to an increased in precipitation through an intensification of the westerlies. After 3500 cal. yr BP, shrub and grass communities became dominant at the expense of Nothofagus forest, suggesting a climatic shift to dry conditions, as a result of weaker westerlies. This patchy forest-steppe vegetation has favoured the occurrence of fire events. Subsequently, Nothofagus forest recovered for a short period between 2000 and 400 cal. yr BP. Then, major vegetation changes took place with the re-establishment of an open landscape. The calculated moisture balance index allowed us to hypothesize about the relationship between westerlies fluctuation and El Niño Southern Oscillation (ENSO) anomalies during the mid and late Holocene.